Construction method and application of standard curve for determining zinc and aluminum oxide in kiln slag of rotary kiln

CN119555716APending Publication Date: 2025-03-04XIN JIANG ZIJIN NON-FERROUS METALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411642786.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-04

Smart Images

  • Figure CN119555716A_ABST
    Figure CN119555716A_ABST
Patent Text Reader

Abstract

The invention relates to a construction method and application of a standard curve for determining zinc and aluminum oxide in kiln slag of a rotary kiln. The construction method comprises the following steps: (1) treating a kiln slag sample of the rotary kiln by adopting an alkali fusion method to obtain a standard sample, and detecting constant values of the content of zinc and aluminum oxide elements in the standard sample; (2) adding boric acid into the kiln slag sample of the rotary kiln, mixing, tabletting to obtain an analysis sample, and measuring the intensity of the X-ray of the analysis sample by using an X-ray fluorescence spectrophotometer; and establishing a working curve of the analysis sample, and calibrating the working curve through the constant value to obtain a standard curve. The construction method and the detection method of the standard curve for determining the zinc and the aluminum oxide in the kiln slag of the rotary kiln are low in cost and rapid. The method is high in accuracy and precision and good in applicability. And the method can meet the production requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical detection and analysis, and in particular to a method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag and an application thereof. Background Art

[0002] The flue gas, smoke, intermediate slag or solution produced during the hydrometallurgical zinc smelting process usually contain a variety of valuable metals. Since heavy metal impurities and their compounds are mostly toxic substances, they are the main industrial pollution sources that pollute the atmosphere, poison water sources and harm the soil, directly threatening human health and survival. In a hydrometallurgical zinc smelting plant, the comprehensive recovery of valuable elements from these intermediate products can not only reduce the harm of furnace gas, smoke and slag, which is beneficial to environmental protection, but also increase the variety and output value of products. Therefore, recovering valuable metals through rotary kilns and improving the comprehensive utilization of resources is one of the important signs of the vitality of zinc smelting plants.

[0003] The rotary kiln can process lead and zinc materials containing oxides and some sulfides and sulfates, mainly to extract zinc and lead. When the rotary kiln processes leached slag, the dried leached slag is mixed with coke powder or anthracite powdered coal and added to a rotary dense body with a certain inclination. When the dense body is driven by an electric motor to rotate at a certain speed, the charge rolls and flows from one end to the other. The high-temperature furnace gas generated by the fuel is opposite to the flow direction of the charge, and the metal oxides in the charge have good contact with the reducing agent and are reduced. The lining of the rotary kiln is composed of high-aluminum castables. The analysis of the aluminum content of the rotary kiln slag has guiding significance for adjusting the process. At the same time, the zinc content in the slag is also an important indicator parameter. When the zinc content of the slag is higher than 6%, it has metal recovery value. The traditional method of analyzing the zinc and aluminum content of the slag is long and costly. Therefore, in order to meet the needs of rapid production detection, it is of great significance to seek a low-cost, fast, and accurate method that can meet production needs for the determination of zinc and aluminum content in the slag. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag and its application. The present invention overcomes the shortcomings of the long process and high cost of chemical analysis methods, and the inability to press rotary kiln slag into analysis samples before treatment, and provides a low-cost and fast detection method with high accuracy, precision and good applicability. A method for determining the content of zinc and aluminum oxide in kiln slag that can meet production needs.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] The first object of the present invention is to provide a method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag, the method comprising the following steps:

[0007] (1) using an alkali fusion method to process a rotary kiln slag sample to obtain a standard sample, and detecting the fixed values ​​of the zinc and aluminum oxide content in the standard sample;

[0008] (2) taking another sample of the rotary kiln slag, adding boric acid to the mixture, pressing the sample into a tablet to obtain an analysis sample, and using an X-ray fluorescence spectrometer to measure the intensity of the X-rays of the analysis sample; establishing a working curve for the analysis sample, and calibrating the working curve using the fixed value to obtain a standard curve.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the specific steps in step (1) are: mixing sodium hydroxide with the rotary kiln slag sample and performing a melting reaction at a high temperature to obtain a standard sample; taking the standard sample and detecting the fixed values ​​of the zinc and aluminum oxide content in the standard sample by an inductively coupled plasma spectrometer.

[0011] Furthermore, the mass ratio of the sodium hydroxide to the rotary kiln slag sample is 15 to 25:1.

[0012] Furthermore, the temperature of the melting reaction is 650°C to 680°C, and the time is 0.5 to 1 hour.

[0013] Furthermore, the specific steps of tableting in step (2) are: using a tablet press to tablet the rotary kiln slag sample and boric acid using a boric acid edging method to obtain an analysis sample; in the analysis sample, the boric acid is located at the substrate and the surrounding edge, and the rotary kiln slag sample is exposed in the middle of the upper surface.

[0014] The beneficial effect of adopting the above further scheme is: since the rotary kiln slag sample is calcined at high temperature in a rotary kiln, the sample is relatively loose and has a high carbon content, it is impossible to directly prepare the sample through a tablet press. A certain proportion of boric acid needs to be added to the sample before it can be pressed into an analytical sample.

[0015] Furthermore, the mass ratio of the rotary kiln slag sample to the boric acid is 1-2:0.5-1.0.

[0016] Furthermore, the thickness of the analysis sample is 3 mm to 6 mm, wherein the thickness of the rotary kiln slag sample is 0.7 mm to 1.2 mm, and the diameter of the exposed area is 27 mm to 30 mm.

[0017] Furthermore, the working pressure of the tablet press is 20T to 30T.

[0018] Furthermore, the tablet press has a holding time of 20s to 30s.

[0019] Further, the specific drawing process of the standard curve is as follows:

[0020] (1) loading the analysis sample into the sample analysis box of the X-ray fluorescence spectrometer, measuring the spectra of Zn and Al elements, and confirming the PHA value;

[0021] (2) Load the samples with fixed values ​​into the X-ray fluorescence spectrometer in sequence, register the element intensities, and draw a standard curve.

[0022] The second object of the present invention is to provide an application of a standard curve for determining zinc and aluminum oxide in rotary kiln slag, wherein a rotary kiln slag sample to be determined is added with boric acid for mixing, and a tablet is pressed to obtain an analysis sample to be determined; an X-ray fluorescence spectrometer is used to determine the intensity of the X-ray, and the content of zinc and aluminum oxide in the rotary kiln slag is obtained according to the standard curve.

[0023] The invention has the following beneficial effects: the standard curve of the invention can be used to simply, quickly and at low cost determine the content of zinc and aluminum oxide in the kiln slag; the relative standard deviation of the zinc and aluminum oxide content in the kiln slag detected is less than 5%, and the method determination lower limit is 0.10%. The method has good accuracy, precision and applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The standard curve diagram constructed for Example 1 of the present invention; wherein (a) is the standard curve diagram of Zn; and (b) is the standard curve diagram of Al. DETAILED DESCRIPTION

[0025] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0026] Example 1: Method for constructing standard curves of zinc and aluminum oxide in rotary kiln slag

[0027] (1) Take the kiln slag numbered 2024.06.0415:40 produced every hour in the rotary kiln for 24 hours, mix them evenly in equal amounts, take 6g of sodium hydroxide and 0.3g of the rotary kiln slag sample, and carry out melting reaction at 665°C for 1 hour to obtain a standard sample. The prepared standard sample is detected by an inductively coupled plasma spectrometer (SPECTRO BLUE; SPECTRO) to determine the fixed values ​​of zinc and aluminum oxide elements in the standard sample;

[0028] (2) Weigh 2.0 g (accurate to 0.0001 g) of the same rotary kiln slag sample numbered 2024.06.0415:40 as in step (1) into a mortar, add 0.6 g of boric acid, grind evenly, and press the rotary kiln slag sample and boric acid on a press machine (ZHY-401B; Beijing Zhonghe) using a boric acid alumina cup at a pressure of 25.0 T using a boric acid edging method for 25 seconds to obtain an analysis sample; in the analysis sample, the boric acid is located at the substrate and the surrounding edge, and the rotary kiln slag sample is exposed in the middle of the upper surface; the thickness of the analysis sample is 5 mm, of which the thickness of the rotary kiln slag sample is 1.0 mm, and the diameter of the exposed area is 28 mm.

[0029] (3) Install the analysis sample into the sample analysis box, use an X-ray fluorescence spectrometer (MXF-2400; Shimadzu) to measure the intensity of its X-rays, and confirm the PHA value: the low PHA value of Zn is 20 and the high PHA value is 110, and the low PHA value of Al is 15 and the high PHA value is 115. Establish a working curve, and load the fixed value standard samples into the X-ray fluorescence spectrometer in sequence, register the element intensity, and draw a standard curve, where the Zn curve equation is Xi (concentration) = 0.008535*li (X-ray intensity) + 0.117012, with a correlation coefficient of 0.999, as shown in Figure 1 As shown; the Al curve equation is: Xi (concentration) = 0.090588 * li (X-ray intensity) + 1.715613, the correlation coefficient is 0.9995, such as Figure 1 shown.

[0030] Example 2: Application of the standard curve for determining zinc and aluminum oxide in rotary kiln slag

[0031] (1) Take 2.0 g (accurate to 0.0001 g) of the rotary kiln slag sample numbered 2024.06.0415:40 in a mortar, add 0.6 g of boric acid, grind evenly, and press the rotary kiln slag sample and boric acid on a press machine (ZHY-401B; Beijing Zhonghe) using a boric acid alumina cup at a pressure of 25.0 T using a boric acid edging method for 20 s to obtain an analysis sample; in the analysis sample, the boric acid is located at the substrate and the surrounding edge, and the rotary kiln slag sample is exposed in the middle of the upper surface; the thickness of the analysis sample is 3 mm, of which the thickness of the rotary kiln slag sample is 0.7 mm, and the diameter of the exposed area is 27 mm.

[0032] (2) The analysis sample was installed in a sample analysis box, and the intensity of the X-rays was measured using an X-ray fluorescence spectrometer (MXF-2400; Shimadzu). The corresponding zinc and aluminum oxide contents were found from the standard curve of Example 1.

[0033] Example 3: Application of the standard curve for determining zinc and aluminum oxide in rotary kiln slag

[0034] This embodiment is the same as Embodiment 2, the only difference being that different samples are tested. The sample tested in this embodiment is rotary kiln slag numbered ZJ2406152-0220:55.

[0035] Example 4: Application of the standard curve for determining zinc and aluminum oxide in rotary kiln slag

[0036] This embodiment is the same as Embodiment 2, the only difference being that different samples are tested. The sample tested in this embodiment is the rotary kiln slag numbered 2024.06.1514:50.

[0037] Comparative Example 1: Application of the standard curve for determining zinc and aluminum oxide in rotary kiln slag

[0038] Standard sample determination: Take the kiln slag numbered 2024.06.0415:40 produced every hour in the rotary kiln for 24 hours, mix them evenly in equal amounts, take 6g of sodium hydroxide and 0.3g of the rotary kiln slag sample, and perform a melting reaction at high temperature to obtain a standard sample. The prepared standard sample is used to detect the determination of zinc and aluminum oxide in the rotary kiln slag sample by an inductively coupled plasma spectrometer (SPECTRO BLUE; SPECTRO).

[0039] Comparative Example 2: Determination of zinc and aluminum oxide content in rotary kiln slag

[0040] This comparative example is the same as comparative example 1, the only difference being that different samples are tested. The sample tested in this comparative example is rotary kiln slag numbered ZJ2406152-0220:55.

[0041] Comparative Example 3: Determination of zinc and aluminum oxide content in rotary kiln slag

[0042] This comparative example is the same as comparative example 1, the only difference being that different samples are tested. The sample tested in this example is the rotary kiln slag numbered 2024.06.1514:50.

[0043] Test example:

[0044] 1. The measured values ​​of Zn and Al2O3 of Examples 2-4 and Comparative Examples 1-3 are shown in Table 1 below;

[0045] 2. The sample of Example 1 was measured 7 times in parallel using the measurement method of Example 2, and the relative standard deviation (RSD) was calculated. The results are shown in Table 2 and Table 3:

[0046] Table 1 Mass percentage of Zn and Al2O3 in samples

[0047] Zn measured value (%) <![CDATA[Al2O3 measurement value (%)]]> Example 1 2.76 5.40 Example 2 2.68 5.51 Example 3 3.58 5.31 Comparative Example 1 2.98 5.25 Comparative Example 2 2.78 5.75 Comparative Example 3 3.76 5.38

[0048] Table 2 Zn mass percentage of samples

[0049]

[0050] Table 3

[0051]

[0052] From Table 1-3 we can get:

[0053] (1) As can be seen from Table 1, the relative errors of the zinc and aluminum oxide data are less than 5%, indicating that the detection method of the present invention has good accuracy.

[0054] (2) As shown in Table 2 and Table 3, the relative standard deviation of the present invention is <5%, and the method accuracy is good, indicating that the detection method of the present invention has reliable measurement results.

[0055] In summary, the present invention overcomes the shortcomings of the long process and high cost of chemical analysis methods, and the inability to press rotary kiln slag into analysis samples after pretreatment, and provides a low-cost and fast method for constructing and detecting standard curves for determining zinc and aluminum in rotary kiln slag, which has high accuracy, precision and good applicability. A method for determining the aluminum content in slag that can meet production needs.

[0056] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag, characterized in that: The method comprises the following steps: (1) using an alkali fusion method to process a rotary kiln slag sample to obtain a standard sample, and detecting the fixed values ​​of the zinc and aluminum oxide content in the standard sample; (2) taking another sample of the rotary kiln slag, adding boric acid to the mixture, pressing the sample into a tablet to obtain an analysis sample, and using an X-ray fluorescence spectrometer to measure the intensity of the X-rays of the analysis sample; establishing a working curve for the analysis sample, and calibrating the working curve using the fixed value to obtain a standard curve.

2. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 1, characterized in that: The specific steps in step (1) are: mixing sodium hydroxide with the rotary kiln slag sample and performing a melting reaction at a high temperature to obtain a standard sample; taking the standard sample and detecting the fixed values ​​of the zinc and aluminum oxide content in the standard sample by an inductively coupled plasma spectrometer.

3. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 2, characterized in that: The mass ratio of the sodium hydroxide to the rotary kiln slag sample is 15-25:

1.

4. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 2, characterized in that: The temperature of the melting reaction is 650° C. to 680° C., and the time is 0.5 h to 1 h.

5. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 1, characterized in that: The specific steps of tabletting described in step (2) are: using a tablet press to tablet the rotary kiln slag sample and boric acid using the boric acid edging method to obtain an analysis sample; in the analysis sample, the boric acid is located at the substrate and the surrounding edge, and the rotary kiln slag sample is exposed in the middle of the upper surface.

6. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 1, characterized in that: The mass ratio of the rotary kiln slag sample to the boric acid is 1-2:0.5-1.

0.

7. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 5, characterized in that: The thickness of the analysis sample is 3 mm to 6 mm, wherein the thickness of the rotary kiln slag sample is 0.7 mm to 1.2 mm, and the diameter of the exposed area is 27 mm to 30 mm.

8. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 5, characterized in that: The working pressure of the tablet press is 20T to 30T.

9. The method for constructing a standard curve for determining zinc and aluminum oxide in rotary kiln slag according to claim 1, characterized in that: The tablet press has a holding time of 20s to 30s.

10. Application of the standard curve for determining zinc and aluminum oxide in rotary kiln slag, characterized in that: The rotary kiln slag sample to be measured is added with boric acid for mixing, and the sample is pressed into a tablet to obtain an analysis sample to be measured; the intensity of the X-ray is measured by an X-ray fluorescence spectrometer, and the contents of zinc and aluminum oxide in the rotary kiln slag are obtained according to the standard curve described in any one of claims 1 to 9.